The trend and features of physician workforce supply in China: after national medical licensing system reform - Chengxiang Tang; Daisheng Tang (BMC, 2018)
Abstract Background The annual number of newly licensed physicians is an important indicator of medical workforce supply, which can accurately reflect an inflow into the health care market over a period. In order to both regulate medical professions and improve the quality of health care services, China established its medical licensing system from the point of the implementation of 'Law on Practising Doctors' in 1999. The objective of this study is to depict the trend and structure of newly licensed physicians thereafter. Methods This study analyses a unique census data set that provides the headcount of newly licensed physicians from 2005 to 2015 in China. We also review a short history of medical licensing system reform in China since the 1990s. Results The annual number of first-time licensed physicians in China increased from 159 489 in 2005 to 221 639 in 2015. Up to 2015, over half of newly licensed physicians had not received a medical education equivalent to a bachelor degree or higher. Around 51% of China's newly licensed physicians were female in 2005, while the same ratio for females in 2015 was 56%. Conclusion This article first provides an exploratory analysis of physician inflow into health care market in China using physician licensing data. The medical licensing system in China allows entering physicians with a broad range of educational levels. Moreover, the feminisation of the physician supply in China has become increasingly apparent and its impacts on health care provision still require more rigorous examination.